Particulate matter and childhood allergic diseases - Song-I Yang (Korean Pediatric Society, 2019)
Particulate matter (PM) is a ubiquitous air pollutant that is a growing public health concern. Previous studies have suggested that PM is associated with asthma development and exacerbation of asthma symptoms. Although several studies have suggested increased risks of atopic dermatitis, allergic rhinitis, and allergic sensitization in relation to PM exposure, the evidence remains inconsistent. The plausible mechanisms underlying these effects are related to oxidative stress, enhancement of sensitization to allergens, inflammatory and immunological responses, and epigenetics. This review discusses the effect of PM on childhood allergic diseases, along with plausible mechanisms. Further studies are required to understand the role of PM exposure on childhood allergic diseases, to reduce these diseases in children.